Sex, then and now: sexualities and the Bible - Loader, William R. G. (Cascade Books, 2022)
How did the biblical authors and the people of their time view sex and sexual issues? This book takes the reader into their world. It offers a careful reading of these ancient texts and how they would have been understood in the context of their time. Did they see sex positively or as something dangerous? How did they view marriage? How do their views of marriage relate to the way most people see marriage today? What were the understandings of human nature that underpinned their discussions of appropriate and inappropriate sexual behavior? How did they view sexual relations between people of the same gender? Listening to biblical writers alongside what others were saying at the time, this book takes these texts seriously. By providing information about sex then it offers the reader a basis for discussing sex now and for approaching issues that have continued to create consternation, confusion, and often conflict in today’s world. At the same time, it provides for possibilities of seeing continuity and appreciating the richness and blessing of human sexuality